A Latina Luthercostal Invitation Into an Ecclesial Estuary. Issue 4 (December 2016) - Ortiz, Leila M.
Abstract: Drawing from ethnographic and meta‐ethnographic research, this article analyzes the hermeneutic, and resulting ecclesiology, of Latina Luthercostal women in Latino/a Lutheran congregations in New York and Philadelphia. Preliminary findings suggest that Latina Luthercostal hermeneutics mirror Martin Luther's own hermeneutical approach. This particular hermeneutical lens invites the church into an ecclesial estuary where seemingly opposed traditions meet and are drawn by the Holy Spirit into a messy, meaningful, and necessary experience of death and resurrection for the purposes of transformation and renewal.